The Effect of Availability Bias and Representativeness Bias on Investment Decisions Among Millennials and Gen Z in Indonesia - Kurniana; Haymans Manurung, Adler; Sembel, Roy (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
The investment represents a more advanced financial activity than solely depositing funds in a bank for safekeeping. The investment is anticipated to mitigate the effect of inflation on the fluctuation of the currency's worth. Millennials and Generation Z are demographic cohorts that significantly affect the capital market; nonetheless, numerous individuals within these generations exhibit imprudent investment behaviour, primarily attributable to biases in their investment decisions. The research aimed to critically examine prior studies employing different methods to further the understanding of availability bias and representativeness bias in Indonesia. The study utilised a quantitative method. The participants of this study consisted of investors from the Gen Z and millennial cohorts in Indonesia. The sample size in this investigation consisted of 120 samples. The sampling technique employed in this study was purposive sampling, namel7 a strategy selecting participants based on predetermined criteria. The study's criteria encompassed individuals classified as investors, falling within the age range of 17 to 35 years, and possessing a minimum of 6 months of expertise in the field of investment. This study's findings indicated that bias availability and bias affected statistically significant and positively affected investment decision-making among millennials and Gen Z individuals in Indonesia. The data revealed that 14.7% of investment decisions are affected by variables related to availability bias and representativeness bias, with the remaining 85.3% being affected by other variables.